PENGARUH PENGETAHUAN, PENGALAMAN DAN KUNTABILITAS AUDITOR TERHADAP KUALITAS AUDIT (STUDI KASUS PADA INSPEKTORAT PROVINSI BENGKULU) - Hernandianto; Ilham Azoni; Yusmaniarti Yusmaniarti (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to examine the influence of auditor knowledge, experience and accountability on audit quality at the Bengkulu provincial inspectorate office. The population in this study consisted of 100 auditors, the sampling technique in this study used saturated sampling (census). This research is quantitative research with primary data. The data analysis technique uses multiple linear regression analysis which is processed using the SPSS (Statistical Product and Service Solution) application. The data collection method is through observation and questionnaires. The partial research results show that knowledge has a significant positive effect on audit quality, this can be seen from the significance value of 0.002 <0.05 and the regression coefficient value of 0.219. Experience has a significant positive effect on audit quality, this can be seen from the significance value of 0.000 < 0.05 and the regression coefficient value of 0.483. Accountability has a significant positive effect on audit quality, this can be seen from the significance value of 0.043 <0.05 and the regression coefficient value of 0.253. The research results simultaneously show that the auditor's knowledge, experience and accountability have a significant positive effect on audit quality, this can be seen from the significance value of 0.000 < 0.05 and the F value of 23,976. Keywords: Knowledge, Experience, Auditor Accountability and Audit Quality